Thermal charge/discharge performance of iron–germanium alloys as phase change materials for solar latent heat storage at high temperatures. (August 2020) - Gokon, Nobuyuki; Jie, Chew Shun; Nakano, Yuya; Kodama, Tatsuya; Bellan, Selvan; Cho, Hyunseok
Highlights: Eutectic/hypereutectic alloys are proposed as a new latent heat storage material. Fe–Ge alloy PCMs can be potentially operated at high-temperatures over 600°C. The alloys are higher latent heat than chloride salts. Graphite play role in passivation/container material for PCMs in inert atmosphere. Abstract: In this study, an iron–germanium alloy (Fe–Ge alloy) was examined as a phase change material at temperatures exceeding 800°C for thermal energy storage in solar thermal applications. The cyclic properties of the thermal charge/discharge of the Fe–Ge alloy were examined at various thermal cycles. A thermal reliability test was performed in the form of a multi-cyclic performance assessment to evaluate the short- and long-term thermal stability of this alloy. Eutectic and hypereutectic chemical compositions of the Fe–Ge alloy were placed in a graphite container under vacuum and an inert atmosphere. The Fe–Ge alloy was experimentally examined for its compatibility with the container material of graphite-carbon. The element distribution of each Fe–Ge alloy was examined via a cyclic performance test. The heat storage capacities were evaluated and compared with those of chloride molten salts. The Fe–Ge alloy exhibits significant potential as a latent heat storage material in next-generation solar thermal applications as it demonstrates various advantages, namely: a higher storage capacity than that of chloride molten salts, temperature followability to the phase diagram, a quick thermal response, satisfactory cyclic behavior of charge/discharge modes, a thermodynamically stable metallographic structure, and non-reactivity with capsulation materials of graphite carbon.